Technological Transformation
XII, 316 p. 1 illus.
Keywords: The philosophical study of technology has acquired only recently a voice in academic conversation. This situation is due, in part, to the fact that technology obviously impacts on "the real world," whereas the favored stereotype of philosophy allegedly does not. Furthermore, in some circles it was assumed that philosophy ought not impinge on the world. This bias continues today in the form of a general dismissal of the growing area now referred to as "applied philosophy". By contrast, the academic scrutiny of science has for the most part been accepted as legitimate for some 30 years, primarily because it has been conducted in a somewhat ethereal manner. This is, in part, because it was believed that, science being pure, one could think (even philosophically) about science without jeopardizing one's intellectual purity. Since World War II, however, practitioners of the metascientific arts have come to ac knowledge that science also shows signs of having touched down on numerous occasions in what can only be identified as the real world. No longer able to keep this banal truth a secret, purists have sought to defuse its import by stressing the difference between pure and applied science; and, lest science be tainted by contact with the world through its applications, they have devoted additional energy to separating applied science somehow from technology.